New records of benthic foraminifera in the surface sediments of the Dulas Bay saltmarsh in North Wales, UK - Ruth Kennedy; Mariann Biro; Fabienne Marret-Davis; Simon Oliver (PANGAEA, 2023)
We investigated the community composition of benthic foraminifera in surface sediments taken from 14 sample sites in the saltmarshes of the Dulas Bay Estuary in North Wales (UK). Constrained cluster analyses determined that the composition and richness of benthic foraminiferal species in our study area were dominated by calcareous species in mud and sandy sediments and that their vertical distribution was constrained by elevation, which is consistent with reports from other latitudinally similar saltmarsh habitats. The exceptionally low proportion of morphological abnormalities in the foraminiferal tests that we sampled suggests that the Dulas Bay Estuary is a pristine unpolluted environment. New micropaleontological occurrence records for the Dulas Bay Estuary are presented, which will be useful for reconstructing Holocene relative sea-level changes and contribute to global databases: PANGAEA® Data Publisher.